Parental first aid literacy in epistaxis: do parents know what to do? - AlZabin, Alya; Almajed, Ebtesam; AlTamimi, Reem; Alqasimi, Nuwayyir Abdullah; Albalawi, Yasser; AlWehaibi, Nasser (Frontiers in Public Health, 2025)
BackgroundEpistaxis is a common otorhinolaryngology emergency, especially among the pediatric population. While prompt first aid is essential, there is limited data on parents’ knowledge regarding its management in Saudi Arabia. This study assessed parental literacy in epistaxis first aid and its correlation with sociodemographic factors.MethodsA cross-sectional online study was conducted from May to June 2023, targeting parents of children aged ≤12 years across Saudi Arabia. Using a structured questionnaire, data on demographic characteristics and epistaxis first aid knowledge were collected from 777 participants. Descriptive statistics and binary logistic regression were utilized for analysis.ResultsThe majority of parents (79%) reported that their child had experienced epistaxis, and 72.7% considered it an emergency. However, knowledge gaps were evident: only 15.8% recognized posterior bleeds as life-threatening, and just 54.8% identified the correct position for managing epistaxis. Geographic disparities were noted, with parents in the South, East, and North showing lower literacy than those in the Western region. Additionally, male, non-Saudi, and postgraduate parents had reduced literacy regarding epistaxis prevention. A large proportion of parents relied on the internet for information, which may contribute to these gaps.ConclusionThere is a significant need for targeted educational programs to improve parental knowledge of epistaxis first aid, particularly among specific demographic groups. Enhancing access to first-aid training and credible resources could improve emergency responses to epistaxis, mitigating risks and promoting safer outcomes for children.